Czech Perspective on the History of Central European University Culture - Czajka, Łukasz (Sensus Historiae, 2025)
Lukáš Fasora and Jiří Hanuš, two Czech historians, demonstrate in their research that the Central European university culture, in countries such as the Czech Republic, Slovakia, or Poland, often developed through difficult struggles against the overpowering influences of German or Russian culture. An example of such an influential idea is the Humboldtian vision of the university, advocating the creation of an autonomous academy free from political, religious, and economic pressures. In the 20th century, the turbulent history of Central European universities revealed two threats to this ideal of academic culture. The first was communist ideology, which destroyed freedom of speech and the autonomy of scientific research. The second challenge for today’s universities are the current higher education reforms, which pave the way for the emergence of corporate institutions of academic capitalism.